Pengaruh Pemanfaatan Perpustakaan Sekolah dan Motivasi Belajar Peserta Didik Terhadap Hasil Belajar pada Mata Pelajaran Bahasa Indonesia Kelas Tinggi SDN Palangka: The Influence of School Library Utilization and Student Learning Motivation on Learning Outcomes in Indonesian Language Subjects for Upper Grade Students of SDN Palangka - Pramudita, Ratri; Bulkani, Bulkani; Kartini, Nurul Hikmah (Anterior Jurnal, 2025)
This study aims to: (1) determine whether there is an influence of utilizing the school library on learning outcomes in the Indonesian Language subject, (2) determine whether there is an influence of students' learning motivation on learning outcomes in the Indonesian Language subject, and (3) determine whether there is a combined influence of utilizing the school library and students' learning motivation on learning outcomes in the Indonesian Language subject. The population in this study consists of fifth and sixth-grade students from public elementary schools in Palangka Raya, Central Kalimantan, totaling 1,117 students from six public elementary schools. The sample for this research includes 285 students, determined according to the Krejcie and Morgan table. The sampling technique used was proportional random sampling.The results of the study indicate that: (1) there is an effect of school library utilization (X1) on learning outcomes in the Indonesian language subject (Y), based on the regression test results, the significance value (p) obtained is 0.001, which is smaller than 0.05 (p < 0.05); (2) student learning motivation (X2) has no effect on learning outcomes in the Indonesian language subject (Y), based on the results of the nonlinear regression test, the significance value (p) obtained is 0.106, indicating that p > 0.05; (3) there is an effect of both school library utilization (X1) and student learning motivation (X2) together on learning outcomes in the Indonesian language subject (Y), based on multiple nonlinear regression analysis, the regression R value is 0.199.